CORRELATION WORK ATTITUDE WITH LOW BACK PAIN (LBP) COMPLAINTS (STUDI ON FISH PORTER IN MUNCAR HARBOR BANYUWANGI) - Saiful Azis Setyawan (Universitas Serambi Mekkah, 2019)
Low back pain (LBP) is one of the complaints that are often encountered in workers, including fish porter. Fish porter are at risk of LBP's complaints, because their work is was did by standing and bent. This study purpose to study the correlation between work attitude with LBP complaints for fish porter (manol) in Muncar Harbor Banyuwangi. This tudy was analytic observational with a cross sectional aprroach. The number of samples in this study amounted 35 respondents and taken from the population amounted 42 respondents using simple random sampling technique. Data collection technique used interview questionnaires to get individual characteristics (age, length of work and smoking habits). REBA and NBM are used to observations work attitude and to determine LBP complaints. Data were analyzed using chi-square test and cross tabulation. The results the most fish porter aged up to 35 years (88,6%) , had length of work period up to five years (80%), moderate smokers category (48,6%). Majority work attitudes were not ergonomic (74.3% ), and 51.4% fish porter experienced LBP complaints. The result of the analysis with the chi-square test showed work attitude had correlation LBP complain (p value 0.042). Keywords: Low back pain, work attitude